An Automatic Data editing and switching system - DAS, S. K.; SUNDARAM, K. (MAUSAM, 1980)
The paper describes an equipment developed for selection and switching of meteorological messages, from the trunk circuit to the subsidiary circuits. The equipment scans different characters present sin the designator of a message using World Meteorological format, by comparing the pulses in the characters of International alphabet 2 with the pulses generated in the equipment and filters data according to pre-determined programme. The basic circuitry of the equipment comprises of a pulse generator or clock, a frequency divider, divider, a comparator and coincidence circuit, a pulse recogniser and a matrix to recognise the character identified.